Preconception Lifestyle Status and Its Predictors in Women Contemplating Pregnancy - Sakineh Ghasemi; Sakineh Mohammad‐Alizadeh‐Charandabi; Mojgan Mirghafourvand (Mashhad University of Medical Sciences, 2018)
Preparation for pregnancy and management of modifiable risk factors result in favorable pregnancy and childbirth outcomes. Regarding this, the present study aimed to determine preconception lifestyle status and its predictors among women contemplating pregnancy. This cross-sectional study was conducted on 201 women aged 18-35 years contemplating pregnancy for the coming year. The data were collected using sociodemographic characteristic form, preconception lifestyle questionnaire, preconception lifestyle awareness questionnaire, and perceived stress scale. Data analysis was performed using Pearson correlation, independent t-test, one-way ANOVA, and multivariate linear regression. The mean preconception lifestyle score was 2.7±0.3 (range: 1-4). According to the results, knowledge about preconception lifestyle, maternal age, receipt of routine preconception care, and marital satisfaction were the predictors of preconception lifestyle. Based on the findings, it is necessary that the health care providers take some measures to improve the preconception lifestyle in women contemplating pregnancy by considering its predictors.